Managing Asthma on the College Campus: Findings of a Texas Pilot Study - Collins, Kevin P; Weiss-Randall, Debra N; Henry, Nicholas R (Respiratory care, 2015)
Students attending institutions of higher education have the option of utilizing their student health center (SHC) for asthma management. However, a review of the available literature revealed no previous research as to how SHCs on college campuses in Texas manage students with asthma. This led to the following research questions; how are SHCs in Texas managing asthma for college students, and what are the SHC directors' attitudes and perceptions of the impact of asthma on their college campuses? This descriptive pilot study randomly selected 20 colleges in Texas; 17 institutions agreed to participate. The inclusion criteria consisted of 4-y colleges accredited by the Southern Association of Colleges and Schools with an undergraduate student population of greater than 1,000 full-time students, excluding online colleges. Once identified, the director of each institution's SHC was contacted by telephone and invited to complete the Managing Asthma on College Campuses Survey instrument via telephone interview (n = 14) or e-mail (n = 3). Descriptive statistics were used to analyze quantitative data and common themes were noted for the qualitative data. Quantitative data obtained through the survey revealed 23.5% of SHCs provide individualized asthma action plans to students and 35% of SHCs stated they have an emergency action plan for asthma exacerbations. Respondents noted 2 major barriers for effective asthma management on campus: lack of understanding of chronic disease management and underuse of the SHC due to a lack of awareness of its existence. Perceived barriers to visiting the SHC included access issues, money, and students self-medicating with short-acting β2 agonist inhalers and/or over-the-counter medications. The majority of directors were satisfied with asthma services provided to students; however, they felt more face-to-face asthma education was needed.